Perspectives on Self-Compassion From Adult Female Survivors of Sexual Abuse and the Counselors Who Work With Them - McLean, Lisa (Journal of interpersonal violence, 2021)
While compassion-focused therapy (CFT) holds significant promise as an intervention for survivors of sexual abuse, a history of abuse can uniquely impact an individual’s capacity to cultivate compassion and may generate a fear of compassion. Understanding the specific perspectives of sexual abuse survivors may inform the application of CFT-based interventions with this client group. Two separate focus groups were established for this purpose, one with adult female survivors of sexual abuse (n = 7) and another with sexual abuse counselors (n = 7). Transcripts were analyzed according to a consensual qualitative research design. Analysis of the survivor focus group identified two core domains, Barriers to Compassion, including poor relational templates, negative perception of self, low coping self-efficacy, and fears, resistance, and misperceptions regarding self-compassion, and Factors Supporting Compassion, including support from others, compassion for others, high coping self-efficacy, motivation and hope for change, and timing and readiness for change. Analysis of the counselor focus group revealed three domains, Therapeutic Factors to Support Compassion, including counselor authenticity and modeling, gradual introduction with consideration to individual needs, acknowledgment of suffering and offering an alternative perspective; Factors Affecting Client Readiness and Capacity, including shame, self-blame, and negative sense of self, response from others, and difficulty in changing self-critical habits; and Anticipated Outcomes, including providing a hope and recovery focus, offering an alternative perspective and coping strategy, and restoring trust. Findings are discussed in relation to clinical implications and relevance to a CFT model of intervention.